2017
DOI: 10.17221/177/2015-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid treatment saves quality and enhances antioxidant properties of apricot fruit

Abstract: The aim of this study was to investigate the effect of three salicylic acid (SA) concentrations (0.5, 1 and 2 mmol/l) on 7 fruit quality attributes of three apricot cultivars ('Flavor Cot' , 'Jumbo Cot' and 'Bergeron') during cold storage (at 1°C for 7, 14, 21 and 28 days). Applications of 1 or 2 mmol/l SA significantly reduced chilling injury and fruit decay of apricot fruit as well as membrane electrolyte leakage and ascorbic acid content. Fruits treated with SA resulted in high total polyphenolic content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The improvement of nutraceutical attributes through the application of biostimulants or elicitors, such as SA, is a response of plants to the stress caused by them, increasing the synthesis of phytochemical compounds [47]. Among the most relevant antioxidants produced by tomato, lycopene is considered a bioactive compound due to its importance related to the antioxidant capacity in vegetables, which is known to increase when secondary metabolism is activated, a condition caused by SA applications [5,48].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of nutraceutical attributes through the application of biostimulants or elicitors, such as SA, is a response of plants to the stress caused by them, increasing the synthesis of phytochemical compounds [47]. Among the most relevant antioxidants produced by tomato, lycopene is considered a bioactive compound due to its importance related to the antioxidant capacity in vegetables, which is known to increase when secondary metabolism is activated, a condition caused by SA applications [5,48].…”
Section: Discussionmentioning
confidence: 99%
“…Increase of these pigments is a common trend during cold storage of apricots regardless of applied treatments, as demonstrated for different treatments: with ethylene blocking substances (Aminoethoxyvinylglycine and 1-methylcyclopropene), CaCl 2 or combination of mentioned compounds [Nagy 2018]. However, increase of carotenoids during cold storage is characteristic of apricots harvested in earlier maturity stages [Fan et al 2018], while for fruits harvested at com-mercial maturity stage Ezzat et al [2017] reported no change in carotenoid content, while Egea et al [2007] claimed an increase of carotenoids during shelf life of apricots previously stored at low temperature.…”
Section: Fruit Compositionmentioning
confidence: 99%
“…2). Increase of total phenol content in apricots during initial phases and its subsequent decrease to initial level was reported by a number of authors [Fan et al 2018, Leccese et al 2012], but the incidence of reduction of total phenols during cold storage was reported too [Ezzat et al 2017]. Conditions of cold storage are very important from the standpoint of total phenol content.…”
Section: Fruit Compositionmentioning
confidence: 99%